From ‘We Are Slavic’ To ‘My sister’s Crown’ : Gender, Ethnicity and Media Events - Panea, José Luis; Pérez-Rufí, José Patricio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This paper analyzes two performances of the Eurovision Song Contest which correspond to the Polish and Czech entries in the 2014 and 2023 editions of the show respectively. In its musical and staging proposal, both of them stir up a debate on Slavic feminine identity since two opposed perspectives. Moreover, these performances coincide with two critical historical moments in Slavic ambit due to the expansionist and identity policies of Kremlin. This research compares how the concepts of sorority and Pan-Slavism are represented from its own actors (in this case, the Slavic women) in the field of media events.